Levels of autonomy in synthetic biology engineering - Jacob Beal; Miles Rogers (Molecular Systems Biology)
Graphical Abstract Engineering biological organisms is a complex process and challenging that could benefit from a combination of standardization and automation. This Commentary discusses the advantages and challenges of achieving high levels of autonomy in synthetic biology.